First-principles Study of Electronic and Magnetic Properties of Two-dimensional Hexagonal Boron Nitride Doped with Germanium and Tin Atoms - Adhikari, Dipak; Panthee, Jeewan; Lamsal, Saurabh; Adhikari, Kapil; Adhikari, Narayan Prasad; Pantha, Nurapathi (Journal of Institute of Science and Technology, 2022)
For the study of geometrical structure, stability, and electronic and magnetic properties of Germanium and tin-doped two-dimensional hexagonal boron nitride (h-BN), First-principles calculations have been carried out. Plane-wave pseudo-potential method in association with the density functional theory (DFT) framework used in Quantum ESPRESSO codes has been implemented to perform the calculations. A 3X3 supercell size substitutional doping of a single Boron or Nitrogen atom was carried out for the study. Pristine h-BN showed non-magnetic behavior with comprehensive gap material having an indirect band gap of 4.64eV. The doping effect of Ge and Sn atoms at the B-site was energetically more favorable than N-site. The defected h-BN sheet was found to be severely distorted with remarkable alteration in bond length and angles around the defected sites. Ge doped h-BN showed semiconducting properties with a reduced band gap in comparison to the insulating nature of pristine h-BN, whereas half metallicity was noticed in Sn doped h-BN system. Both the systems showed a magnetic moment of 1.0 µB.